Programa Cultura Viva: do Governo Federal à Prefeitura de São Paulo - Teixeira, Vinicius Ribeiro Alvarez (2017)
The present work discusses the relationship between State and culture, especially regarding to the called popular traditional cultures. Thereby, it also approaches concepts and precepts that in somehow influence the debate and the course of cultural policies, national or international. As a research object, the study emphasizes the analysis of the themes addressed in the Programa Cultura Viva. The study aimed to understand the path of the program from the policy formulation, in the Ministry of Culture, to its implementation by the city of São Paulo